National Victim Assistance Agency Survey, 1992 - McEwen, J. Thomas ([Verlag nicht ermittelbar], 1995)
This data collection examines victim assistance programs that are operated by law enforcement agencies, prosecutor's offices, and independent assistance agencies. Victim assistance programs came into being when it was discovered that, in addition to the physical, emotional, and financial impact of a crime, victims often experience a "second victimization" because of insensitive treatment by the criminal justice system. Specifically, this study sought to answer the following questions: (1) What are the current staffing levels of victim assistance programs? (2) What types of victims come to the attention of the programs? (3) What types of services are provided to victims? and (4) What are the operational and training needs of victim assistance programs? The survey was sent to 519 police departments, sheriff departments, and prosecutor's offices identified as having victim assistance programs. Also, 172 independent full-service agencies that were believed to provide referral or direct services to victims (not just advocacy) were also sent surveys. Variables on staffing levels include the number of full-time, part-time, and volunteer personnel, and the education and years of experience of paid staff. Victim information includes the number of victims served for various types of crime, and the percent of victims served identified by race/ethnicity and by age characteristics (under 16 years old, 17-64 years old, and over 65 years old). Variables about services include percent estimates on the number of victims receiving various types of assistance, such as information on their rights, information on criminal justice processes, "next-day" crisis counseling, short-term supportive counseling, or transportation. Other data gathered include the number of victims for which the agency arranged emergency loans, accompanied to line-ups, police or prosecutor interviews, or court, assisted in applying for state victim compensation, prepared victim impact statements, notified of court dates or parole hearings, or made referrals to social service agencies or mental health agencies. Information is also presented on training provided to criminal justice, medical, mental health, or other victim assistance agency personnel, and whether the agency conducted community or public school education programs. Agencies ranked their need for more timely victim notification of various criminal justice events, improvement or implementation of various forms of victim and public protection, and improvement of victim participation in various stages of the criminal justice process. Agencies also provided information on training objectives for their agency, number of hours of mandatory pre-service and in-service training, types of information provided during the training of their staff, sources for their training, and the priority of additional types of training for their staff. Agency variables include type of agency, year started, and budget information.